2015
DOI: 10.1016/j.jobaz.2015.09.003
|View full text |Cite
|
Sign up to set email alerts
|

Cardiac disorders and mode of action of the Egyptian scorpion venom Androctonus bicolor on isolated toad’s heart

Abstract: Scorpion venom is a complex mixture of components with various pharmacological and toxicological effects. It is characterized by the presence of a large number of toxins that specifically interact with ion channels of excitable cells. The Egyptian scorpion Androctonus bicolor belongs to the family of Buthidae and until now no information is available about the effect of its venom on cardiac muscles. Using an in vitro approach, cardiotoxicity and mode of action of A. bicolor venom on isolated toad's heart were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 54 publications
0
2
0
Order By: Relevance
“…The bioactivities of Hemiscorpius lepturus peptides discovered in specific fractions constitute novel biomolecules with potential pharmacological use [ 84 ]. Different neurotoxins in scorpion venom are accountable for the various envenomation effects in humans, especially cardiotoxic peptides that cause severe cardiorespiratory complications to envenomation victims [ 85 ]. To identify the cardiotoxic component of Hemiscorpuis lepturus venom, bioassay-guided fractionation was employed.…”
Section: Implementation Of Separation Methods For Scorpion Venomsmentioning
confidence: 99%
“…The bioactivities of Hemiscorpius lepturus peptides discovered in specific fractions constitute novel biomolecules with potential pharmacological use [ 84 ]. Different neurotoxins in scorpion venom are accountable for the various envenomation effects in humans, especially cardiotoxic peptides that cause severe cardiorespiratory complications to envenomation victims [ 85 ]. To identify the cardiotoxic component of Hemiscorpuis lepturus venom, bioassay-guided fractionation was employed.…”
Section: Implementation Of Separation Methods For Scorpion Venomsmentioning
confidence: 99%
“…Various cardiac disorders were recorded such as sinus arrhythmias, ectopic beats, and different degrees of heart blockage. The findings indicated that the venom of A. bicolour directly influenced the cardiac electrical activity of toads through β‐adrenergic receptors (Abdel‐Rahman, Ayed, Abdel‐Mottaleb, Omran, & Nabil, 2015).…”
Section: Effect Of Scorpion Toxins On Excitable Tissue Disordersmentioning
confidence: 99%